D-mannose alleviates chronic periodontitis in rats by regulating the functions of neutrophils - Xue Li; Xueting Chen; Qingyu Zhu; Pengye Zhang; Shunxue Nan; Lei Lv; Shengcai Qi (BMC Oral Health)
Abstract Background Periodontitis is a chronic inflammatory disease characterized by the destruction of the components of the periodontium. It significantly impacts oral health and has been linked to systemic conditions like cardiovascular disease and diabetes. The critical role of neutrophils in the occurrence and development of chronic periodontitis has been paid increasing attention. The study aimed to explore the protective effects of D-mannose on chronic periodontitis and determine whether its underlying mechanisms is related to neutrophils. Methods To explore the protective effects of D-mannose on chronic periodontitis, the eight-week-old Sprague Dawley rat model of lipopolysaccharide (LPS)-induced periodontitis was established, followed by D-mannose treatment by oral gavage. To evaluate the protective effects of D-mannose against periodontal bone loss, methylene blue staining, hematoxylin and eosin (H&E) staining, and micro-CT scanning were utilized. Then, immunofluorescence (IF), Western Blot, and RT-PCR were applied to assess the expression levels of pro-inflammatory cytokines (IL-1β, IL-6, and IL-17), anti-inflammatory cytokine (IL-10), tumor necrosis factor-alpha (TNF-α), granulocyte colony-stimulating factor (G-CSF), granulocyte-macrophage colony-stimulating factor (GM-CSF), ten-eleven translocation 2 (TET2), and key glycolytic enzymes (HK1, HK2, PFKFB3), and to examine D-mannose’s impact on the recruitment and activation of neutrophils in the gingiva. Additionally, neutrophils isolated from the peripheral blood of healthy rats were treated with LPS and D-mannose, and changes in the expression levels of myeloperoxidase (MPO), IL-1β, IL-6, IL-17, IL-10, and TET2 were observed via IF. Results In vivo, D-mannose inhibited LPS-induced alveolar bone resorption in rats. After D-mannose treatment, the expression levels of IL-17 (p<0.01) and TET2 (p<0.01) were suppressed by IF, and the expression levels of IL-1β (p<0.05), IL-17 (p<0.05) and TET2 (p<0.01) were downregulated by WB. The results of qPCR showed that D-mannose reduced the expression levels of IL-1β (p<0.05), IL-6 (p<0.01), IL-17 (p<0.01), TNF-α (p<0.01), G-CSF (p<0.01), GM-CSF (p<0.01), TET2 (p<0.01), HK1 (p<0.01), HK2 (p<0.01), and PFKFB3 (p<0.01). D-mannose also inhibited the recruitment and activation of neutrophils in LPS-treated rat gingival tissues. In vitro, the results of IF showed that D-mannose inhibited the activation of neutrophils stimulated by LPS, downregulated the expression of IL-1β (p < 0.05), IL-6, IL-17 (p < 0.01), and TET2 (p < 0.01), and upregulated the expression of IL-10 (p < 0.01). Conclusions D-mannose can alleviate chronic periodontitis in rats by regulating the functions of neutrophils, potentially associated with the expression of TET2 and glycolysis, providing new insights into the potential application of D-mannose to chronic periodontitis.